2020
DOI: 10.3390/w12113009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Slope of Growing Trays on Productivity of Wheat Green Fodder by a Nutrient Film Technique System

Abstract: Application of hydroponic systems in feed production has not been extensively studied. Therefore, there is insufficient data on the effect of the slope of hydroponic growing trays used in the nutrient film technique on wheat fodder yield and its qualitative parameters. The slope of the trays has only been studied for food crops. This study conducted experimental research using a nutrient film technique hydroponic fodder growing device to evaluate the impact of growing tray slope angle on hydroponic wheat fodde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Not only the flow rate and container size, but also the plant spacing [32] and position impact the characteristics of the flow field in hydroponics. Furthermore, the optimum flow pattern may also be linked with the width, slope [33], and length [14] of the cultivation container, as these will affect the solution depth and root aeration [28]. The relationship between these factors should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Not only the flow rate and container size, but also the plant spacing [32] and position impact the characteristics of the flow field in hydroponics. Furthermore, the optimum flow pattern may also be linked with the width, slope [33], and length [14] of the cultivation container, as these will affect the solution depth and root aeration [28]. The relationship between these factors should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Irrigation through sprinklers was scheduled for 15 s every four hours, with the photoperiod consisting of 10 h/6 h light/dark cycles. Previous research has shown that water without added nutrients can support the hydroponic growth of fodder for a period of seven days [23]. The experimental design included four treatments with varied light intensities at 0 µmol/m 2 /s (L0, control treatment), 100 µmol/m 2 /s (L1), 200 µmol/m 2 /s (L2), and 300 µmol/m 2 /s (L3).…”
Section: The Design Of the Controllable Environmental Cultivation Sys...mentioning
confidence: 99%
“…Wheat, barley and fodder hydroponic were tested and are still under investigation; good amounts of fodder were produced using hydroponic systems [71][72][73]. Cereals may be grown hydroponically [74,75], or in assisted open fields. Figure 8 shows the predicted maximum average temperatures and amounts of rainfall in Jordan as zones.…”
Section: Strategic Crops In Jordanmentioning
confidence: 99%